Effect of Cutting Fluid on Micromilling of Ti-6Al-4V Titanium Alloy - Ziberov, M.; Silva, M. B. D.; Jackson, Mark; Hung, W. N. P. (My University, 2017)
This paper studies the micromilling of Ti-6Al-4V titanium alloy. The main objective of this work is to study the performance of micromill tools in terms of burrs, machined surface and tool wear in machining of Ti-6Al-4V titanium alloy and evaluate the effect of the application of cutting fluid. Experimental micromilling tests with 152.4 μm diameter WC tools were made. The tests were carried out on a four axis CNC milling machine with maximum spindle speed of 60,000 rpm and a resolution of 0.1 μm. To measure the burr height, a profilometer with 1.0 mm measuring range and 16 nm resolution was used. The samples and tools were observed under scanning electron microscope to evaluate the machined surface quality, to measure wear and to analyse wear mechanisms. The results show that the application of cutting fluid has a large effect on the quality of the machined parts, both in terms of burrs formed and in terms of machined surface quality. Depending on the cutting conditions, the relative size of the burrs formed is much higher than in macromachining operations. Built up edges on cutting tool affects tool life and surface finish. © 2016 The Authors
Citation: Ziberov, M., Silva, M. B. D., Jackson, M., & Hung, W. N. P. (2016). Effect of Cutting Fluid on Micromilling of Ti-6Al-4V Titanium Alloy. Procedia Manufacturing, 5, 332-347. doi:10.1016/j.promfg.2016.08.029
Keywords: Built Up Edge.; Micromachining; Micromilling; Ti-6Al-4V